2019
DOI: 10.1021/acs.orglett.9b00128
|View full text |Cite
|
Sign up to set email alerts
|

Formylation of Fluoroalkyl Imines through Visible-Light-Enabled H-Atom Transfer Catalysis: Access to Fluorinated α-Amino Aldehydes

Abstract: A visible-light-enabled catalytic formylation of fluoroalkyl imines is developed. With readily accessible starting materials and organocatalysts, this method provides a general approach to masked fluoroalkyl amino aldehydes. A synergistic catalytic effect between the photosensitizer and the H atom transfer agent was proven pivotal to this transformation. After removing the mask, free aldehydes can be obtained and further converted to various β-fluoroalkyl β-amino alcohols, which are attractive building blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…In 2019, Lu, Gong, and co-workers reported a photocatalytic, redox-neutral net formylation reaction of fluoroalkyl imines, with 1,3-dioxolane serving as a formyl equivalent ( Scheme 326 ). 894 The optimal reaction conditions require the use of 2,3-butanedione and N -hydroxysuccinimide (NHS), which were found to be the most efficient organic photocatalyst and HAT reagent for this transformation, respectively. In total, 29 examples were reported, affording various α-amino 1,3-dioxolanes in yields of 51–96%.…”
Section: Reductive Transformations Of Carbonyls Imines and Other X=y Functional Groups Through Photochemical And Electrochemical Pcet Promentioning
confidence: 99%
“…In 2019, Lu, Gong, and co-workers reported a photocatalytic, redox-neutral net formylation reaction of fluoroalkyl imines, with 1,3-dioxolane serving as a formyl equivalent ( Scheme 326 ). 894 The optimal reaction conditions require the use of 2,3-butanedione and N -hydroxysuccinimide (NHS), which were found to be the most efficient organic photocatalyst and HAT reagent for this transformation, respectively. In total, 29 examples were reported, affording various α-amino 1,3-dioxolanes in yields of 51–96%.…”
Section: Reductive Transformations Of Carbonyls Imines and Other X=y Functional Groups Through Photochemical And Electrochemical Pcet Promentioning
confidence: 99%
“…Su et al reported dioxolanylation-triggered cascade cyclizations, in which α,α-disubstituted acrylamides were employed to generate indoline products (Scheme c) . Gong and Lu reported the radical-chain formylation of imines; HAT initially occurred via O-centered radical derived from N -hydroxysuccinimide and 2,3-butadione (Scheme d). , …”
mentioning
confidence: 62%
“…Lastly, hydrogen atom transfer (HAT) has also been used in order to perform the C-H activation of different alkyl radical precursors and perform the desired alkylation reaction with activated imines (Scheme 7). Lu and Gong reported the α-oxyalkyl radical addition of 1,3-dioxolane to fluoroalkyl imines (Scheme 7, top) [19,20], while Dilman managed to install different alkyl and acyl radicals into N-sulfonyl imines (Scheme 7, bottom) [21][22][23]. Scheme 6.…”
Section: O Ho O [Glycosyl Carboxylic Acids] [Activation With Tcnhpi]mentioning
confidence: 99%